(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines the linguoculturological characteristics of place names related to the tourism sector in the French language. It analyzes the toponymic layers within the names of tourism objects, as well as issues regarding the history of their origin and etymology.